Making a Video of Counseling Service Flow at Puspaga Bauntung Batuah to The Community of Banjarmasin City - Winda Pebriani; Herlina Herlina; Mahdia Fadhila; Siti Faridah; Nazwa Adibah (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Informative videos of short duration through social media are increasingly being done. Since the Covid-19 outbreak hit the world, restrictions on social activities have been imposed so that more activities are carried out at home, which has caused the duration of people accessing electronic media and social media to increase. Making a video of the flow of counseling services at Puspaga Bauntung Batuah to the people of the City of Banjarmasin is a means to socialize the flow of registration for counseling services in this place because one of the problems that work partners have is the lack of information provided to the community about how to get the services contained in Puspaga Bauntung Batuah as a service unit provided by the government. Making a video of the counseling service flow at the Bauntung Batuah Puspaga is intended as a medium to inform the public about the registration process to take part in counseling at the Bauntung Batuah Puspaga, Banjarmasin City. Then also promotional media so the people of Banjarmasin want to do counseling or consultation on problems as a preventive tool so that there is no violence in the family.